Overview of Waste Final Processing Place (TPA), Kubu Raya: A Descriptive Study - Hajimi Hajimi; Muhammad Rizki Fauzi; Salbiah Salbiah (Yayasan Ahmad Mansyur Nasirah, 2024)
The Kubu Raya landfill uses an open dumping system in its operations. (This method is no longer recommended for use in Indonesia). In this research, we describe the conditions surrounding the Kubu Raya TPA using observational methods and interviews with a descriptive approach. We describe landfill operations, infrastructure and facilities, daily waste volume, Kubu Raya landfill resources, remaining land, and service life. We also discuss future landfill land needs. The Kubu Raya landfill uses an open dumping system and does not practice vector control. The leachate collection facilities don't function, and the landfill's existing facilities and infrastructure need improvement. We have 270 m3 of waste entering Kubu Raya landfill each day, with a workforce of 37. The landfill covers 270 ha, and its remaining service life is approximately 300.84 days. In Kubu Raya Regency, it is necessary to consider adding 14.6 ha of land or building a new landfill. We need vector control efforts, infrastructure improvements, and considerations for additional land to make Kubu Raya TPA's waste management more environmentally friendly and efficient.